Döntés preferálással: Felvételi vizsgák a felsőoktatásban 1967 és 1989 között Magyarországon (Szociológiai Szemle, 2024)
The selective mechanism present at the entrance exams may be an important component of the chances o f acquiring higher qualifications. This is studied in the paper during the period between 1967 and 1989 in Hungary, on the basis o f an all round data collection. As contrasted to some research results obtained before, the present survey shows that despite the disappearance of the quota system introduced in higher education in the 50s, students of worker and peasant background were preferred at the entrance exams all along in the late Kádár period of Hungary, or, the extent of giving preference to them was stronger than if the examiners only wanted to compensate the disadvantages due only to poorer examination results. Preference accorded to boys as against girls could also be demonstrated in most of the years of the period, though this is less significant than the preferential treatment of those coming from a working class background. However, it remains an open question how far the selective mechanism, present at the entrance exams, could counter-balance differences in the inclination to further studies in higher education, or at the earlier stages.